2021
DOI: 10.1002/hep.31700
|View full text |Cite
|
Sign up to set email alerts
|

Eradication of Chronic HCV Infection: Improvement of Dysbiosis Only in Patients Without Liver Cirrhosis

Abstract: It is well accepted that liver diseases and their outcomes are associated with intestinal microbiota but causality is difficult to establish. The intestinal microbiota is altered in patients with hepatitis C. As chronic HCV infection can now be cured in almost all patients, it is an ideal model to study the influence of liver disease on the microbiota. We aimed to analyze prospectively the changes in the gut microbiome in patients who received direct acting antivirals (DAA) and achieved sustained virological r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
19
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(22 citation statements)
references
References 51 publications
2
19
0
1
Order By: Relevance
“…and Bifidobacterium spp. increased significantly 6-12 months after the achievement of SVR only in non-cirrhotic patients [42]. This confirms that treatment with DAAs can improve the gut microbiota profile in the shortterm, especially in the early stage of liver disease, while in cirrhotic patients restoration of the gut microbiota may require more time.…”
Section: Hepatitis C Virus (Hcv)supporting
confidence: 62%
“…and Bifidobacterium spp. increased significantly 6-12 months after the achievement of SVR only in non-cirrhotic patients [42]. This confirms that treatment with DAAs can improve the gut microbiota profile in the shortterm, especially in the early stage of liver disease, while in cirrhotic patients restoration of the gut microbiota may require more time.…”
Section: Hepatitis C Virus (Hcv)supporting
confidence: 62%
“…After treatment, the composition of the gut and oral microbiota in patients with mild fibrosis without cirrhosis was found to be similar to that of healthy individuals. Treatment-induced changes in the α-diversity were observed predominantly only in patients with a less advanced disease [ 117 , 118 , 119 , 120 , 121 , 122 , 123 ]. These results emphasize the importance of early therapeutic interventions for improving liver function by regulating the gut microbiota composition.…”
Section: Hepatitis Virusmentioning
confidence: 99%
“…Ponziani et al described that cure of HCV infection in patients with cirrhosis is associated with modification of the gut microbiota, but does not improve intestinal barrier function 43 . Wellhöner et al reported that HCV eradication in CHC patients was associated with changes in the microbiome, which were only seen in patients without liver cirrhosis 44 . As our current and previous reports have been limited to studying the state during HCV infection, 17 the characteristics of the microbiome and bile acid metabolism after HCV elimination, especially in patients with cirrhosis, require clarification in a future study.…”
Section: Discussionmentioning
confidence: 99%
“…42 Recently, 2 reports on the microbiome of CHC patients after HCV elimination have been published. 43,44 Ponziani et al described that cure of HCV infection in patients with cirrhosis is associated with modification of the gut microbiota, but does not improve intestinal barrier function. 43 Wellhöner et al reported that HCV eradication in CHC patients was associated with changes in the microbiome, which were only seen in patients without liver cirrhosis.…”
Section: In Vivo Gut-microbiota-liver Axis During Hcv Infection In a ...mentioning
confidence: 99%